The Potential of Ecotourism in Bayan Village's Customary Forest, North Lombok Regency - Anwar, Hairil; B, Kornelia Webliana; Valentino, Niechi; Ichsan, Andi Chairil; Prasetyo, Andrie Ridzki; Amin, Fitrah Maulidi; Azizah, Lutfiah; Jemarut, Wihelmus (PT FORMOSA CENDEKIA GLOBAL, 2024)
Bayan Village, North Lombok District has four customary forests, namely Mandala Customary Forest, Pengempokan Customary Forest, Tiu Rarangan Customary Forest, and Bengket Bayan Customary Forest. The four customary forests have the potential to be developed with the concept of ecotourism. This study uses a qualitative descriptive method. With the determination of the location and respondents using Purposive Sampling. The study was conducted with the aim of analyzing the feasibility of developing Customary Forests into one of the ecotourism attractions using the parameters of ecotourism appeal, accessibility, conditions of the surrounding area, accommodation, facilities and infrastructure and the availability of clean water. The research parameters used the Guidelines for Analysis of Natural Tourism Attraction Operation Areas (ADO-ODTWA) stipulated by the Director General of Forest Protection and Nature Conservation (Dirjen PHKA) in 2003. The results of the study showed that the four tourist attractions in Bayan Village have the potential to be developed into ecotourism destinations, with respective index values, namely Mandala Customary Forest 86.83%, Pengempokan Customary Forest 84.03%, Bangket Bayan Customary Forest 87.69% and Tiu Rarangan Customary Forest 84%